Rapid detection of methicillin-resistant Staphylococcus aureus strains not identified by slide agglutination tests. - Kuusela, P (1994)
Seventy-nine methicillin-resistant Staphylococcus aureus (MRSA) strains, isolated during 1980 to 1990, were classified as MRSA Aggl- (14 strains) and MRSA Aggl+ (65 strains) strains on the basis of test results in slide agglutination assays designed to detect fibrinogen-binding protein (clumping factor) and protein A on the staphylococcal surface. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis revealed that lysostaphin digests of MRSA Aggl- strains contained a high-molecular-weight protein which was not detected in digests of MRSA Aggl+ strains. Immunization of rabbits with an MRSA Aggl- strain produced an antiserum which agglutinated all MRSA Aggl- strains and also 64 of 65 MRSA Aggl+ strains. Only 1 of 68 coagulase-negative staphylococci showed agglutination in this assay. The anti-MRSA Aggl- antiserum reacted mainly with a 230-kDa staphylococcal surface protein but also with a 175-kDa protein, probably formed by proteolysis of the former and a few slightly smaller proteins. These could not be immunologically detected in lysostaphin digests of MRSA Aggl+ strains. Purified antibodies reacting with the 230-kDa protein agglutinated all MRSA Aggl- strains, indicating that the protein is located on the surfaces of staphylococci. The results suggest a tentative role for the 230-kDa protein or its fragments as a novel target to develop more efficient rapid identification methods for S. aureus, including MRSA.